Pemberian Tablet Fe Dan Jus Jambu Biji Pada Remaja Putri Yang Anemia Defisiensi Besi - Hastuti Marlina; Winda Putriyana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: Iron deficiency anemia is a decrease in hemoglobin concentration (<12 g / dL) Due to the reduced provision of iron resulting in the formation of red blood cells (erythrocytes) is disturbed. Young women have the highest risk of suffering from anemia aged 13-18 years with a prevalence of 22.7% Objective: This study attempts to knowing the difference in levels of hb adolescent girls who had iron deficiency by the provision of a tablet fe and the juice of guava in public junior high schools 2 rengat 2015. Method: The kind of research is analytic with the design quasy experiment using pretest-posttest randomized control group design. The analysis used is analysis of univariat bivariat and with test and test t-dependen t-independen. The population is the students of all class VII and VIII public junior high schools 2 rengat with samples from the students of 34 who had iron deficiency anemia who is in bundle up in the control group and 17 the students of the treatment group the students of 17. The control group given tablets fe and the treatment group given tablets fe and the juice of guava provided for 7 days. Result: The results showed an average of Hb levels in the control group before the intervention and after 10.612 10.506 while average Hb levels in treatment group before and after the intervention 10.576 10.918 with an average difference of 0.10 and 0.34. P value of 0.811 and 0.317> 0.05 Conclusion: there was no significant difference in mean hemoglobin levels between the control and treatment groups, however, judging from the average difference between the control group and the treatment occurs trend increase in the average hemoglobin concentration is 0.24. Keywords: Anemia Iron Deficiency, Provision of a Tablets Fe, Provision of a Tablets Fe And Guava Juice